Nitrogen-doped carbon nanofibers derived from polypyrrole coated bacterial cellulose as high-performance electrode materials for supercapacitors and Li-ion batteries. (20th August 2016) - Lei, Wen; Han, Lili; Xuan, Cuijuan; Lin, Ruoqian; Liu, Hongfang; Xin, Huolin L.; Wang, Deli
Graphical abstract: Highlights: Nitrogen-doped carbon nanofiber (NDCN) was synthesized. The NDCN has a unique 3D interconnected network structure. The NDCN exhibits enhanced capacitance behaviors and high long-term stability. Abstract: Nitrogen-doped carbon nanofiber (NDCN) was synthesized via carbonization of polypyrrole (PPy) coated bacterial cellulose (BC) composites, where BC serves as templates as well as precursor, and PPy serves as the nitrogen source. The synthesized NDCN was employed as electrode for both supercapacitors and Li-ion batteries. The large surface area exposed to electrolyte resulting from the 3D carbon networks leads to sufficient electrode/electrolyte interface and creates shorter transport paths of electrolyte ions and Li + ion. Besides, the three types of N dopants in NDCN improve the electronic conductivity, as well as superior electrochemical performance.